Antibiotics: environmental impact and degradation techniques - Bulut, Duygu Takanoğlu; Kuran, Özkur; Koluman, Ahmet (İdris Karagöz, 2024)
Our reliance on antibiotics, life-saving medications that combat bacterial infections, has inadvertently introduced them into the environment. This paper explores the environmental consequences of this unintended release, focusing on the persistence of antibiotics and their disruption of ecological balance. We delve into the rise of antibiotic-resistant bacteria as a major public health concern linked to this environmental contamination. Recognizing the limitations of existing degradation techniques, the paper emphasizes the need for innovative solutions. We explore the potential of novel materials like engineered nanoparticles and biochar alongside investigating unconventional degradation mechanisms found in extreme environments. Ultimately, the paper underscores the importance of collaborative research efforts and the development of sustainable solutions to mitigate the environmental impact of antibiotics and safeguard the future effectiveness of these critical medications.

Antibiyotiklere olan bağımlılığımız, bakteriyel enfeksiyonlarla mücadelede hayati öneme sahip olan ilaçların, istenmeyen bir şekilde çevre kirliliğine sebep olmasına da yol açmıştır. Bu çalışma, bu istem dışı salınımın çevresel sonuçlarını inceleyerek, antibiyotiklerin kalıcılığını ve ekolojik dengeyi bozmasını ele almaktadır. Antibiyotiklere dirençli bakterilerin yayılması, bu çevresel kirlilikle ilişkili olarak önemli bir halk sağlığı sorunu olarak göz önünde bulundurulmaktadır. Mevcut indirgeme tekniklerinin sınırlılıklarının farkında olarak, bu çalışma yenilikçi çözümlerin gerekliliğini vurgulamaktadır. Mühendislikle üretilmiş nanoparçacıklar ve biyokömür gibi yeni materyallerin potansiyelini incelemekte ve ayrıca zorlu ortamlarda bulunan geleneksel olmayan indirgeme mekanizmalarını araştırmaktadır. Sonuç olarak, bu çalışma, antibiyotiklerin çevresel etkisini azaltmak ve bu kritik ilaçların gelecekteki etkinliğini korumak için işbirlikçi araştırma çabalarının ve sürdürülebilir çözümlerin geliştirilmesinin önemini vurgulamaktadır.
Antibiyotikler: çevresel etkileri ve indirgeme teknikleri
Keywords: Wastewater Treatment Processes; Atıksu Arıtma Süreçleri [EN] Water Treatment Processes; Su Arıtma Süreçleri